Study on the effect of smoking on Type 2 Diabetic Patients in Federal Medical Center Owerri, Southeastern Nigeria - Nwaokoro, Joakin Chidozie; Okorie, Ede Alison; Chima, O Emerole; Sally, NO Ibe; Amadi, AN; Dozie, INS; Iwuji, SC; Nwaokoro, AA (Asian Journal of Medical Sciences, 2014)
Background: Diabetes is an umbrella term for a number of metabolic diseases that affects the body’s ability to control blood glucose levels. The hormone insulin is produced in the pancreas, and helps to metabolize glucose for energy. Diabetes occurs when insulin production is impaired. Objective: The present study was to examine the effect of smoking on type 2 diabetic patients visiting Federal Medical Centre. Materials and Methods: The sample size was 97 respondents while the major instrument for data collection was a well constructed, validated and reliably tested questionnaire, including observations made on secondary existing record data of the hospital. Data obtained was analyzed using frequency distribution, means, standard deviation and fisher’s exact test. Results: Results of the study indicated that majority of the diabetic patients 78(80.4%) were non smokers, while 8(8.2%) and 11(11.3%) respondents were current and past smokers respectively. Maintainance of good glycaemic control should be considered as the therapeutic goal for prevention of diabetic complications. Conclusion: A comprehensive programmes should be initiated to prevent smoking in type 2 diabetic patients such as: regular physical activity, health education on diabetes, smoking cessation, home blood sugar monitoring - minimize smoking impact to body organs that may lead to many complications. Asian Journal of Medical Science, Volume-5(3) 2014: 63-71 DOI: http://dx.doi.org/10.3126/ajms.v5i3.8950